"Say no to bad touches": Schools, sexual identity and sexual violence in northern Uganda. (March 2015) - Porter, Holly E.
Graphical abstract: Highlights: Details of sex are left deliberately vague by trusted adults. Children learn by doing, and often this is instigated by boys. Schools reinforce subordinate gender roles where violence is an ever-present possibility. Consent is absent as a distinction between appropriate and illicit sex. Effects on girls of messages intended to empower them are feelings of blame, shame and silence. Abstract: This article explores the role of schools in the formation of sexual identities and incidence of sexual violence in the Acholi sub-region of northern Uganda, a conflict and post-conflict setting. It reflects three years of participant observation and in-depth interviews with 187 women, and primarily draws on interviews with 17 teachers in five primary schools. The evidence shows how the experience girls have in school builds a paradoxical paradigm with irreconcilable dimensions. Girls are charged to take control of their bodies and sexuality. Simultaneously, they are scripted into feminine sexual identities that reinforce subordinate gender roles where violence is an ever-present possibility. Boys learn masculine notions of sexuality that emphasize paternity and customary exchanges while consent is downplayed. The study highlights the burden of responsibility often placed on both educators and girls through emphasis on their agency and power. This occurs without due acknowledgment for how these are constrained, particularly in extreme settings such as conflict and post-conflict contexts. It calls for programs to ensure engagement with structural constraints, broader focus on gender relations and specific attention to boys and violent expressions of masculinity.